2012
DOI: 10.3109/01480545.2011.619193
|View full text |Cite
|
Sign up to set email alerts
|

Methanol poisoning in Iran, from 2000 to 2009

Abstract: Methanol poisoning continues to be a serious problem in Iran; however, there is not yet any report of the prevalence of methanol intoxication. This report is a descriptive study of methanol intoxication in Iran. We performed a cross-sectional analysis of 51 patients with methanol intoxication who were admitted to Noor Hospital affiliated with Isfahan University of Medical Science (Isfahan, Iran) from January 2000 to December 2009. Characteristics of the participants, including age, sex, amount of methanol inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 10 publications
4
41
0
1
Order By: Relevance
“…In all the studies examining the prevalence of methanol poisoning (5,15,16), experience has shown that methanol poisoning still causes a wide range of side effects (17). This issue is vital due to the delays in hospitalization and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In all the studies examining the prevalence of methanol poisoning (5,15,16), experience has shown that methanol poisoning still causes a wide range of side effects (17). This issue is vital due to the delays in hospitalization and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sale, production, and consumption of alcoholic beverages are legally prohibited in Iran, there is a high possibility of profiteering and fraud in their production. There is not any detailed report available on the amount of alcohol consumption in Iran, but the increase in alcohol poisoning and even death indicates that substandard and counterfeit alcoholic beverages have targeted the young population's health (5). Alcoholic beverages are among the preparations that have taken the lives of many people to date and sometimes lead to their intoxication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical guidelines for methanol poisoning management recommend using an antidote (ethanol or fomepizole), intravenous (IV) sodium bicarbonate, folic or folinic acid, and often haemodialysis (1, 2, 13). This poisoning can be intentional and unintentional, isolated and epidemic (7,11,12,(14)(15)(16)(17) (12,(18)(19)(20). To date, several studies have been performed to identify the prognostic factors of mortality in methanol poisoning (5, 7, 11, 14-16, 18, 20, 21).…”
mentioning
confidence: 99%